Predictors of homelessness among vulnerably housed adults in 3 Canadian cities: a prospective cohort study. (December 2016) - To, Matthew; Palepu, Anita; Aubry, Tim; Nisenbaum, Rosane; Gogosis, Evie; Gadermann, Anne; Cherner, Rebecca; Farrell, Susan; Misir, Vachan; Hwang, Stephen
Abstract Background Homelessness is a major concern in many urban communities across North America. Since vulnerably housed individuals are at risk of experiencing homelessness, it is important to identify predictive factors linked to subsequent homelessness in this population. The objectives of this study were to determine the probability of experiencing homelessness among vulnerably housed adults over three years and factors associated with higher risk of homelessness. Methods Vulnerably housed adults were recruited in three Canadian cities. Data on demographic characteristics, chronic health conditions, and drug use problems were collected through structured interviews. Housing history was obtained at baseline and annual follow-up interviews. Generalized estimating equations were used to characterize associations between candidate predictors and subsequent experiences of homelessness during each follow-up year. Results Among 561 participants, the prevalence of homelessness was 29.2 % over three years. Male gender (AOR = 1.59, 95 % CI: 1.14–2.21) and severe drug use problems (AOR = 1.98, 95 % CI: 1.22–3.20) were independently associated with experiencing homelessness during the follow-up period. Having ≥3 chronic conditions (AOR = 0.55, 95 % CI: 0.33–0.94) and reporting higher housing quality (AOR = 0.99, 95 % CI: 0.97–1.00) were protective against homelessness. Conclusions Vulnerably housed individuals are at high risk for experiencing homelessness. The study has public health implications, highlighting the need for enhanced access to addiction treatment and improved housing quality for this population.